For the Love of Summer - Mallery, Susan (Toronto, Ontario : Harlequin Books, 2024)
"As the owner of Twisted, Seattle's best salons, Erica knows that the sharpest cuts come from the people we love. All it takes to blow up Allison's happy life is one collect call. From prison. Her beloved husband, Peter, has been arrested, leaving Allison pregnant, broke, scared and alone with a toddler. But when her stepdaughter ferrets out the truth, the teen rushes to the last person Allison wants to ask for help--her husband's battle-ax ex. Erica would do anything for Summer, even take in the woman her daughter loves like a second mom. Allison feels intimidated by Erica--a woman who would never let herself become so dependent on a man. But the more time they spend together, the more Allison realizes what Erica truly needs is a friend. Can two women who married the same man move beyond their complicated past and rethink what it means to be family? "
new book 2024 summer.
Keywords: Families -- Fiction; Pregnant women -- Fiction; Stepdaughters -- Fiction; Life change events -- Fiction; Female friendship -- Fiction; Domestic fiction; Marriage & Divorce; Friendship; Domestic fiction